(untitled) (Medicine Today, 2022)
Introduction: The permanent maxillary central incisor is the most visible tooth in the mouth and endodontic treatments are frequently performed in maxillary incisors. Over-instrumentation may cause periradicular inflammation, postoperative pain, and inhibition of the healing process. Working length (WL) determination and maintenance is therefore of major importance. Materials and Methods: This prospective study was conducted in Dhaka Dental College & Hospital, Dhaka from May 2013 to November 2013. A total of 39 cases were included in this study. For electronic method of WL determination iPex NSK (Japan) was used. The radiographic working length was determined by evaluating the position of the end of the file in the canal on the radiograph and it was 0.5 to 1.0 mm short of radiological apex. Results: Pain (94.9%) and trauma (56.4%) were the most common history among the study population. In clinical findings, caries was the most common (56.4%) than swelling was present in 35.9% cases and discoloration was in 30.8% cases. In all cases we found single root of maxillary central incisors. Mean working length (WL) of our study population by apex locator was 21.423±1.259 and by radiograph it was 21.397±1.176; there was no statistically significant difference in WL between these two methods (p=0.743). Conclusion: According to radiographic method working length of our study population was 21.39 mm. WL of our study population was found to be less than the values found by the other studies population like Caucasians, African, Sinhalese, Mongolian and Korean. Medicine Today 2022 Vol.34(2): 83-87